2003
DOI: 10.1063/1.1534936
|View full text |Cite
|
Sign up to set email alerts
|

Systematic design of antireflection coating for semi-infinite one-dimensional photonic crystals using Bloch wave expansion

Abstract: We present a systematic method for designing a perfect antireflection coating (ARC) for a semi-infinite one-dimensional (1D) photonic crystal (PC) with an arbitrary unit cell. We use Bloch wave expansion and time reversal symmetry, which leads exactly to analytic formulas of structural parameters for the ARC and renormalized Fresnel coefficients of the PC. Surface immittance (admittance and impedance) matching plays an essential role in designing the ARCs of 1D PCs, which is shown together with a practical exa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…On the other hand, a 1D rugate profile composed of periodically located Gaussian peaks was considered in [10] as an EBG structure. The behaviour of the transmittance and reflectance of such a profile is characterized, at least in part, by the same features as that of conventional 1D PBG/EBG structures, which are associated with piecewise-homogeneous (layered) materials, as well as that of structures which consist of periodically located mismatched layers showing a graded permittivity profile within any period (see, for example, [11][12][13]). …”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, a 1D rugate profile composed of periodically located Gaussian peaks was considered in [10] as an EBG structure. The behaviour of the transmittance and reflectance of such a profile is characterized, at least in part, by the same features as that of conventional 1D PBG/EBG structures, which are associated with piecewise-homogeneous (layered) materials, as well as that of structures which consist of periodically located mismatched layers showing a graded permittivity profile within any period (see, for example, [11][12][13]). …”
Section: Introductionmentioning
confidence: 92%
“…2 Several studies about the electromigration of flip-chip solder joints have been reported. [3][4][5][6][7][8][9][10] Current crowding especially has a strong effect at the entrance spot of the Al trace into the solder joint, and it is thus the main factor responsible for the failure near the chip/anode side in most solder joints. 4,5 However, the Joule heating effect also occurs during accelerated electromigration tests.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, the Joule heating effect also occurs during accelerated electromigration tests. [6][7][8][9][10] The temperature increase due to the Joule heating effect can be over 30 C when a solder bump is stressed by a 1.0 A current. [5][6][7] Therefore, the Cu column under-bump-metallization (UBM), a structure with a thick UBM, was developed in order to alleviate both the current crowding and the Joule heating effect in flip-chip solder joints under normal operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…where J is an integer, and λ is the wavelength of incident light in a vacuum [15], [16]. Hence, the wavelength of minimum reflectivity is 4n AR t when J is zero.…”
Section: Optical Properties Of Tso Filmsmentioning
confidence: 99%
“…To investigate the AR characteristics of TSO films, TSO (1, 2), (1, 1), (2, 1), and (3, 1) films were each deposited on an Si substrate. Figure 3(b) shows the reflection spectra of TSO/Si samples, where the minimum reflectivity is nearly zero for all samples.When an AR coating layer with thickness t and index of refraction n AR is placed on a substrate with an index of refraction n sub , the reflectivity would be zero for normal incident light when the following conditions are satisfied:where J is an integer, and λ is the wavelength of incident light in a vacuum [15], [16]. Hence, the wavelength of minimum reflectivity is 4n AR t when J is zero.…”
mentioning
confidence: 99%